1996
DOI: 10.1039/cc9960002311
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel three-dimensional oligopyrrole: tris(bipyrro)methane

Abstract: The synthesis, characterization and X-ray structure of the novel three dimensional tris(bipyrr0)methane 3 is reported; this species is predisposed to self-assemble into a cryptandlike dimer in both organic solution and the solid state.Compounds containing three pyrrole units bonded via the aposition to an sp3 hybridized carbon have been known for at least 80 years.] Dubbed tripyrrylmethanes (e.g. 1) Corwin and co-workers2 proposed these species as intermediates in the formation of dipyrromethenes after the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…[113] Später berichteten Sessler et al über eine Serie von b-substituierten Sapphyrinen mit einem oder mehreren Heteroatomen, von denen das Monooxasapphyrin stabile aromatische Komplexe (151) bildete, in denen eine Uranyleinheit in der Porphyrinebene liegt (Abbildung 33). [114] Das Schwefelanalogon 152 des 22p-Pentaphyrins wurde von Vogel und Mitarbeitern beschrieben. [115] Da die Synthesemethoden und die bemerkenswerten Eigenschaften bereits in anderen Übersichten erläutert wurden, [100,101,116] fassen wir hier nur die aktuellsten Ergebnisse zu kernmodifizierten expandierten Porphyrinen zusammen.…”
Section: Kernmodifizierte Expandierte Porphyrineunclassified
“…[113] Später berichteten Sessler et al über eine Serie von b-substituierten Sapphyrinen mit einem oder mehreren Heteroatomen, von denen das Monooxasapphyrin stabile aromatische Komplexe (151) bildete, in denen eine Uranyleinheit in der Porphyrinebene liegt (Abbildung 33). [114] Das Schwefelanalogon 152 des 22p-Pentaphyrins wurde von Vogel und Mitarbeitern beschrieben. [115] Da die Synthesemethoden und die bemerkenswerten Eigenschaften bereits in anderen Übersichten erläutert wurden, [100,101,116] fassen wir hier nur die aktuellsten Ergebnisse zu kernmodifizierten expandierten Porphyrinen zusammen.…”
Section: Kernmodifizierte Expandierte Porphyrineunclassified
“…Porphyrins are also macrocycles that are recognized as excellent cation complexation agents, particularly for cations of the late transition series 16. While structurally characterized U IV and Th IV porphyrin complexes have been reported,17 the expanded porphyrins appear more attractive as ligands18 for the specific purpose of actinyl cation coordination, and a select few, such as alaskaphyrin ( 2 ), oxasapphyrin ( 3 ), and pentaphyrin ( 4 ), have been shown to complex uranyl cations effectively 1921. A uranyl complex of so‐called “super phthalocyanine” was also reported early on 22…”
Section: Methodsmentioning
confidence: 99%
“…The uranyl center is shifted towards the quaterpyrrolic subunit; as such, the coordination environment of the uranium ion is best described in terms of a distorted hexagonal bipyramid. The U−O bond length of 1.760(2) Å is typical for a UO 2 2+ unit,1921 which indicates that no reduction of the metal center occurred. The average U−N bond length of 2.63(1) Å is comparable to that found in the hexacoordinate uranyl complex of alaskaphyrin (2.63(3) Å) 20.…”
Section: Methodsmentioning
confidence: 99%
“…These latter complexes typically exploit the larger cavity size and greater number of nitrogen donor atoms present in expanded porphyins (relative to the porphyrins). In early studies, uranyl complexation was observed in the case of Alaskaphyrin, [19] oxasaphyrrin, [20] pentaphyrrin, [21] and amethyrin. [22] In 2001, the Sessler group reported the synthesis and characterization of hexaphyrin(1.0.1.0.0.0) (isoamethyrin; 1 ; Scheme 1) and its ability to complex the actinide ions uranyl (UO 2 2+ ) and neptunyl (NpO 2 + ).…”
Section: Oligopyrrolic Receptors and Colorimetric Sensors For Actinidesmentioning
confidence: 99%